2001
DOI: 10.1002/1521-3765(20010504)7:9<1936::aid-chem1936>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Solvated CH5+ in Liquid Superacid

Abstract: The transition states for methane activation in liquid superacid have been studied by experimentally determined secondary kinetic deuterium isotope effects (SKIEs) and computational chemistry. For the first time, the SKIEs on hydrogen/deuterium exchange of methane have been measured by using the methane isotopologues in homogeneous liquid superacid (2HF/SbF5). To achieve high accuracy of the SKIEs, the rate constants for pairs of methane isotopologues were simultaneously measured in the same superacid solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 78 publications
2
45
0
Order By: Relevance
“…However between 270 and 315 8C the observed rate constant of deuterium incorporation into methane increased steadily ( Figure 2) going from 4.21 Â10 À6 s À1 at 270 8C to 8.41 Â10 À5 s À1 at higher than the values obtained previously in the very strong superacid H(D)F/SbF 5 . In a recent study of methane reactivity in DF/SbF 5 (15 mol % SbF 5 ) at À 20 8C, we [26] found a free energy of activation of 78.6 kJ mol À1 for this reaction. In the late 1960s Hogeveen and co-workers [8] reported an activation energy of 75 kJ mol À1 for the inverse reaction of dedeuteration of CH 3 D in HF/SbF 5 at high pressure (7 atm) over a temperature interval from À 10 8C to 258C.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…However between 270 and 315 8C the observed rate constant of deuterium incorporation into methane increased steadily ( Figure 2) going from 4.21 Â10 À6 s À1 at 270 8C to 8.41 Â10 À5 s À1 at higher than the values obtained previously in the very strong superacid H(D)F/SbF 5 . In a recent study of methane reactivity in DF/SbF 5 (15 mol % SbF 5 ) at À 20 8C, we [26] found a free energy of activation of 78.6 kJ mol À1 for this reaction. In the late 1960s Hogeveen and co-workers [8] reported an activation energy of 75 kJ mol À1 for the inverse reaction of dedeuteration of CH 3 D in HF/SbF 5 at high pressure (7 atm) over a temperature interval from À 10 8C to 258C.…”
Section: Resultssupporting
confidence: 69%
“…The hydrogen exchange between methane and other acidic species, such as H 3 O , [31] H 2 F (HF) n , [26] SbF 5 /HF, [32] Sb 2 F 11 / HF, [33] and zeolites, [29] have previously been investigated theoretically (Figure 7). The protonating species are both neutral and cationic species and the charge influences the structure of the exchange transition state.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The carbonium mechanism, in particular, is seeing increased research interest, with new experiments [11][12][13][14][15][16][17] but particularly with computational chemistry methods. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Carbonium ions, or protonated alkanes, were first detected in mass spectrometry experiments 36 and have been spectroscopically detected only in the gas phase.…”
Section: Introductionmentioning
confidence: 99%